2022
DOI: 10.3389/fendo.2022.975560
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of giant pituitary tumors requiring surgery

Abstract: ObjectiveThe management of giant pituitary tumors is complex, with few publications and recommendations. Consequently, patient’s care mainly relies on clinical experience. We report here a first large series of patients with giant pituitary tumors managed by a multidisciplinary expert team, focusing on treatments and outcome.MethodsA retrospective cohort study was conducted. Giant pituitary tumors were defined by a main diameter > 40mm. Macroprolactinomas sensitive to dopamine agonists were excluded. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
4
0
1
Order By: Relevance
“…This finding could be due to the soft consistency of an adenoma, making gross total resection achievable. 27 28 A more friable tumor that can easily be aspirated can present an easier experience with achieving gross total resection. 28 Consequently, a firmer tumor with a fibrous texture can be more challenging to fully remove, and therefore, warrant a longer surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding could be due to the soft consistency of an adenoma, making gross total resection achievable. 27 28 A more friable tumor that can easily be aspirated can present an easier experience with achieving gross total resection. 28 Consequently, a firmer tumor with a fibrous texture can be more challenging to fully remove, and therefore, warrant a longer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…27 28 A more friable tumor that can easily be aspirated can present an easier experience with achieving gross total resection. 28 Consequently, a firmer tumor with a fibrous texture can be more challenging to fully remove, and therefore, warrant a longer surgery. 28 Other barriers to a gross total resection of pituitary tumors can be the anatomical location of the tumor, specifically if it has a greater suprasellar extension or cavernous sinus invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this is controversial as other studies have shown no correlation (48), probably because of the difference in the tumor subtypes. Hypopituitarism is a frequent complication in large/giant pituitary adenoma surgery (8, 49,50). It could be challenging to reproduce and identify the worsening or recovery of each anterior pituitary hormonal axis.…”
Section: Discussionmentioning
confidence: 99%
“…З огляду на велетенський розмір та інвазію в шлуночкову систему, радикальне видалення ВАГ пов'язано з високим ризиком пошкодження навколишніх структур, що може призвести до глибокої інвалідізації хворих [3,10,22,23,24,25].…”
unclassified